Investigation of treatment satisfaction and health-related quality of life after add-on to metformin-based therapy in patients with type 2 diabetes - Chang, Yu-Wen; Shen, Feng-Chin; Chen, Chung-Yu (Frontiers in Public Health, 2023)
Background The complexity of oral antidiabetic drug (OAD) regimens affects the quality of life (QOL) and treatment satisfaction. However, data on the QOL of patients with type 2 diabetes mellitus (T2DM) receiving metformin-based OAD treatment in Asia are limited. Therefore, this study aimed to evaluate the QOL and treatment satisfaction and explore the influencing factors and their correlations among patients with T2DM receiving metformin-based OADs. Methods This was a cross-sectional study conducted at the Outpatient Department of Metabolism and Endocrinology at a medical center in Taiwan. Data were collected using the Audit of Diabetes-Dependent Quality of Life (ADDQoL) and the Chinese version of the Satisfaction with Oral Anti-Diabetic Agent Scale (C-SOADAS) questionnaires from patients with T2DM using metformin. The outcomes were analyzed by group and stratified based on the use of two, three, and more than three OADs. The level of agreement between the questionnaires was analyzed using Spearman’s rank correlation coefficient. Results A total of 153 patients with T2DM using metformin were included in this study. The average weighted impact score in the ADDQoL was −2.11, with no significant differences between the three groups. The C-SOADAS score showed a significant difference between the groups using two, three, and more than three OADs (21.42 [1.98] vs. 20.43 [2.09] vs. 19.00 [2.24], p < 0.0001). The ADDQoL and C-SOADAS scores showed low correlations between patients’ QOL and treatment satisfaction. However, the impact of diabetes on specific aspects of life was negatively correlated with the total C-SOADAS scores. Conclusion In Taiwan, a significantly greater effect on QOL was observed among patients with fewer OAD classes and higher treatment satisfaction. This study provides local evidence from self-reporting outcomes of patients with T2DM. Further studies focusing on different populations and treatment regimens for QOL are needed.